If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2(x+5)=3(4-x)
We simplify the equation to the form, which is simple to understand
2(x+5)=3(4-x)
Reorder the terms in parentheses
+(+2x+10)=3*(4-x)
Remove unnecessary parentheses
+2x+10=+3+*(+4-x+)
Reorder the terms in parentheses
+2x+10=+(+12-3x)
Remove unnecessary parentheses
+2x+10=+12-3x
We move all terms containing x to the left and all other terms to the right.
+2x+3x=+12-10
We simplify left and right side of the equation.
+5x=+2
We divide both sides of the equation by 5 to get x.
x=0.4
| (14/x)=7/6 | | 24x+1=2x+4 | | 8-7(1-6r)=-17 | | 6x=20-20y | | 9w-12=24 | | 16a^5b^6+4ab^4-24ab^6= | | 9(2w-8)=18w-72 | | 20+X=180 | | 14x+84=10x+90 | | 3n/2-n/46 | | y-2x=175 | | 84x^2-20xy+28x= | | 14-2x=7-3x | | x/18=4.5/1 | | 0=-1E-06x^2+41.901x-4E+08 | | (11x+33)=(15x-5) | | Y-5x=7 | | Y=-1E-06x^2+41.901x-4E+08 | | 16x(-5x+9)=64 | | 2-4y=10 | | -6n^2+8n=5 | | 9(x-6)+6=9x-6(6-x) | | 4x-14-2x=10 | | Log[12](x)+log[12](x+1)=1 | | 3X+x+5+X=180 | | 9x^2+6x-63=0 | | 8x+3=4x-9+3x+x | | 4v-8=34 | | Y-6=3(x+1) | | 3X+X=X+5 | | g-939/-9=5 | | 9((x^2-x)-4)+4=9(x^2-x)-4(4-(x^2-x)) |